Altering sphingolipid composition with aging induces contractile dysfunction of gastric smooth muscle via KCa1.1 upregulation. Issue 6 (20th August 2015) - Choi, Shinkyu; Kim, Ji Aee; Kim, Tae Hun; Li, Hai‐yan; Shin, Kyong‐Oh; Lee, Yong‐Moon; Oh, Seikwan; Pewzner‐Jung, Yael; Futerman, Anthony H.; Suh, Suk Hyo
Summary: KC a 1.1 regulates smooth muscle contractility by modulating membrane potential, and age‐associated changes in KC a 1.1 expression may contribute to the development of motility disorders of the gastrointestinal tract. Sphingolipids (SLs) are important structural components of cellular membranes whose altered composition may affect KC a 1.1 expression. Thus, in this study, we examined whether altered SL composition due to aging may affect the contractility of gastric smooth muscle (GSM). We studied changes in ceramide synthases (CerS) and SL levels in the GSM of mice of varying ages and compared them with those in young CerS2‐null mice. The levels of C16‐ and C18‐ceramides, sphinganine, sphingosine, and sphingosine 1‐phosphate were increased, and levels of C22, C24:1 and C24 ceramides were decreased in the GSM of both aged wild‐type and young CerS2‐null mice. The altered SL composition upregulated KC a 1.1 and increased KC a 1.1 currents, while no change was observed in KC a 1.1 channel activity. The upregulation of KC a 1.1 impaired intracellular Ca 2+ mobilization and decreased phosphorylated myosin light chain levels, causing GSM contractile dysfunction. Additionally, phosphoinositide 3‐kinase, protein kinase Cζ, c‐Jun N‐terminal kinases, and nuclear factor kappa‐B were found to be involved in KC a 1.1 upregulation. Our findings suggest that age‐associated changes in SL composition or CerS2 ablation upregulate KC a 1.1 via the phosphoinositide 3‐kinase/protein kinase Cζ /c‐Jun N‐terminal kinases/nuclear factor kappa‐B‐mediated pathway and impair Ca 2+ mobilization, which thereby induces the contractile dysfunction of GSM. CerS2‐null mice exhibited similar effects to aged wild‐type mice; therefore, CerS2‐null mouse models may be utilized for investigating the pathogenesis of aging‐associated motility disorders.